2017
DOI: 10.1093/hmg/ddx145
|View full text |Cite
|
Sign up to set email alerts
|

A frequent oligogenic involvement in congenital hypothyroidism

Abstract: Congenital hypothyroidism (CH), the most frequent form of preventable mental retardation, is predicted to have a relevant genetic origin. However, CH is frequently reported to be sporadic and candidate gene variations were found in <10% of the investigated patients. Here, we characterize the involvement of 11 candidate genes through a systematic Next Generation Sequencing (NGS) analysis. The NGS was performed in 177 unrelated CH patients (94 gland-in-situ; 83 dysgenesis) and in 3,538 control subjects. Non-syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
95
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 39 publications
16
95
1
2
Order By: Relevance
“…Thus, those examined as athyreosis could not be excluded for the likelihood of ectopy. Similarly, other studies have found variants associated with dH in patients with athyreosis (30,32). in addition, 2 individual variants in genes associated with pituitary development or central cH (PROP1 and TRHR) respectively were found in 1 cH patient with GiS and 1 patient with Td, and both variants co-occurred with genetic variants associated with DH.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, those examined as athyreosis could not be excluded for the likelihood of ectopy. Similarly, other studies have found variants associated with dH in patients with athyreosis (30,32). in addition, 2 individual variants in genes associated with pituitary development or central cH (PROP1 and TRHR) respectively were found in 1 cH patient with GiS and 1 patient with Td, and both variants co-occurred with genetic variants associated with DH.…”
Section: Discussionsupporting
confidence: 57%
“…Because of the wide phenotypic variation of either thyroid hypoplasia or ectopy, it is conceivable to think that these abnormalities could be determined by variation of quantitative traits, that is, thyroid cells growth and migration, respectively, as a result of polygenic effects. Targeted NGS studies in TD patients' cohorts highlighted that heritable mutations accounts for at least 50% of patients . Moreover, according to what was revealed using mouse models, a significant proportion of patients have multiple gene variations in more than one thyroid specific gene.…”
Section: Discussionmentioning
confidence: 97%
“…Targeted NGS studies in TD patients' cohorts highlighted that heritable mutations accounts for at least 50% of patients. 86 Moreover, according to what was revealed using mouse models, 46 a significant proportion of patients have multiple gene variations in more than one thyroid specific gene. Importantly, some TD candidate gene variations highlighted so far can be assessed also in the general population with a significantly lower prevalence, 15 indicating that the of pathogenesis of TD can be due to the sum of multiple rare alleles that act in concert to generate the pathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are already documented in the literature for TD (Deladoëy et al , ; Magne et al , ). Finally, the genetics of TD remains complex with mutations in more than nine known genes and both classical and complex modes of inheritance, such as a suggested oligogenic model by Persani et al (de Filippis et al , ). The same genetic pattern of inheritance is also observed in other endocrine‐related disorders such as congenital hypogonadotropic hypogonadism (Boehm et al , ) or in the more complicated genetic model of Bardet–Biedl syndrome (Muller et al , ).…”
Section: Discussionmentioning
confidence: 99%